TARGETS FOR MAJORITY OF DRUGS: G PROTEIN-COUPLED RECEPTORS - THEIR STRUCTURE AND INTERACTIONS WITH BIOLIGANDS - JERZY CIARKOWSKI; CEZARY CZAPLEWSKI; MARTA PASENKIEWICZ-GIERULA (TASK Quarterly, 2021)
G protein-coupled receptors (GPCRs) are the most frequent targets for many drugs. They form the largest superfamily of integral membrane proteins, of which more than 1000 members have the following common features: (i) All GPCRs form 7 hydrophobic a-helices of length -38A (25 amino acids, 7 turns) along a single chain. The consecutive helices alternatively cross the membrane, starting from the extracellular side, so that they form a heptahelical transmembrane domain interwoven with 6 loops, of which the even ones plus the N-terminus create the receptor’s extracellular domain while the odd ones plus the C-terminus form its intracellular domain, (ii) All GPCRs are stimulated by diverse extracellular (primary) signals, (iii) Stimulated GPCRs convey the primary signals via their transmembrane and intracellular domains to the cytosolic peripheral heterotrimeric GTP-binding proteins (G proteins), mediating the signal’s further transduction to various cellular second messenger systems. A current status of structural studies on GPCRs, consisting of low -7.5A resolution experimental structures and supplementary molecular modelling, is outlined. Subsequently, some results of authors’ own work on studying essential interactions of the V2 vasopressin renal receptor (V2R) with its agonist [Arg8]Vasopressin (AVP) and selected antagonists are presented, as well as their possible impact on the biological signal transduction is discussed. Finally, perspectives for future developments are sketched.